Hydrogen-rich saline resuscitation alleviates inflammation induced by severe burn with delayed resuscitation. Issue 2 (March 2015) - Wang, Xiaojuan; Yu, Pan; YongYang; Liu, Xiaocong; Jiang, Jinheng; Liu, Degui; Xue, Gang
Abstract Severe burns with delayed resuscitation are associated with high morbidity which is attributed to ischemia–reperfusion injury. This study was undertaken to investigate the effect of hydrogen-rich saline known as a significant selective antioxidant on the inflammatory reaction induced by severe burns with delayed resuscitation. By establishing the model of severe burns with delayed resuscitation in rats, we recorded improvement on the mortality, secretion of cytokines and reaction of oxidative stress of rats treated with hydrogen-rich saline. We found that resuscitation by hydrogen-rich saline alleviated inflammation significantly. We further detected the change of the key nuclear factor NF-κB contributed to inflammation. The expression of both NF-κB and phosphorylated NF-κB in rats having severe burns with delayed resuscitation by hydrogen-rich saline was lower than that in rats with delayed resuscitation with Ringers' solution. Our data imply that hydrogen-rich saline significantly improves the inflammatory reaction in rats with severe burns with delayed resuscitation, possibly by inhibiting activation of NF-κB.